2014
DOI: 10.1021/es402636u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disinfectant, Water Age, and Pipe Materials on Bacterial and Eukaryotic Community Structure in Drinking Water Biofilm

Abstract: Availability of safe, pathogen-free drinking water is vital to public health; however, it is impossible to deliver sterile drinking water to consumers. Recent microbiome research is bringing new understanding to the true extent and diversity of microbes that inhabit water distribution systems. The purpose of this study was to determine how water chemistry in main distribution lines shape the microbiome in drinking water biofilms and to explore potential associations between opportunistic pathogens and indigeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
160
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(176 citation statements)
references
References 56 publications
11
160
1
4
Order By: Relevance
“…The study confirmed the results of Wang demonstrating that the material from which the water supply network is made of can have a significant effect on the amount, frequency and type of biofilm formation, the presence of pathogens as well as the effectiveness of used disinfectants [18].…”
Section: E3s Web Of Conferencessupporting
confidence: 86%
“…The study confirmed the results of Wang demonstrating that the material from which the water supply network is made of can have a significant effect on the amount, frequency and type of biofilm formation, the presence of pathogens as well as the effectiveness of used disinfectants [18].…”
Section: E3s Web Of Conferencessupporting
confidence: 86%
“…It has been reported that the formation of bacterial biofilm contributes significantly to antibiotic resistance (Stewart and Costerton, 2001). The drinking water must be free of pathogenic infectious agents, however it has been observed that it has a variety of microorganisms, including bacteria forming biofilm in distribution systems (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that contribute significantly to the development of them are: ineffective concentration of disinfectants, pH and water temperature, residence time of the water in the tanks and piping, tube construction material. So the drinking water loses quality along its passage through the water supply pipes (Wang et al, 2014). The presence of bacteria in water pipes indicates the poor quality of water and water is a vehicle for diffusion of pathogenic bacteria (Chaves-Simões and Simões, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria as a principal phylum in drinking water is 216 well documented in the literature (Lautenschlager et al 2014;Wang et al 2014;Liu et al 2014;Lührig 217 et al 2015). The average relative abundance of Proteobacteria was 92%.…”
Section: Bacterial Population Comparisons 213mentioning
confidence: 91%